Associations of 12‐year sleep behaviour trajectories from childhood to adolescence with myopia and ocular biometry during young adulthood. (22nd October 2021) - Stafford‐Bell, Nicholas; McVeigh, Joanne; Lingham, Gareth; Straker, Leon; Eastwood, Peter R; Yazar, Seyhan; Mackey, David A; Lee, Samantha Sze‐Yee
Abstract: Purpose: Cross‐sectional studies have variably reported that poor sleep quality may be associated with myopia in children. Longitudinal data, collected over the ages when myopia develops and progresses, could provide new insights into the sleep‐myopia paradigm. This study tested the hypothesis that 12‐year trajectories of sleep behaviour from childhood to adolescence is associated with myopia during young adulthood. Methods: At the 5‐, 8‐, 10‐, 14‐ and 17‐year follow‐ups of the longitudinal Raine Study, which has been following a cohort since their birth in 1989–1992, participants' parents/guardians completed the Child Behaviour Checklist questionnaire (CBCL), which collected information on their child's sleep behaviour and quality. The CBCL includes six questions measuring sleep behaviour, which parents rated as 0 = not true, 1 = somewhat/sometimes true, or 2 = very/often true. Scores were summed at each follow‐up to form a composite "sleep behaviour score". Latent Class Growth Analysis (LCGA) was used to classify participants according to their 12‐year trajectory of sleep behaviour. At the 20‐year follow‐up, an eye examination was performed which included cycloplegic autorefraction and axial length measurement. Results: The LCGA identified three clusters of participants based on their trajectory of sleep behaviour: those with minimal' (43.6% of the total Raine Study sample), 'declining' (48.9%), or 'persistent' (7.5%) sleep problems. A total of 1194 participants had ophthalmic data and longitudinal sleep data available for analysis (47.2% female, 85.6% Caucasian). No significant differences were observed in regards to age, sex, ethnicity or ocular parameters between trajectory groups. Unadjusted and fully adjusted analyses demonstrated that sleep problem behaviour was not significantly associated with changes in refractive error, axial length or corneal radius. Conclusions: Our findings do not support the hypothesis that there is an association between sleep behaviour and myopia. Future longitudinal studies should explore sleep trajectory data pre‐ and post‐myopia diagnosis to confirm our results.